Novel arabinan and galactan oligosaccharides from dicotyledonous plants - Wefers, Daniel; Tyl, Catrin E.; Bunzel, Mirko (Frontiers in Chemistry, 2014)
Arabinans and galactans are neutral pectic side chains and an important part of the cell walls of dicotyledonous plants. To get a detailed insight into their fine structure, various oligosaccharides were isolated from quinoa, potato galactan, and sugar beet pulp after enzymatic treatment. LC-MS2 and one- and two-dimensional NMR spectroscopy were used for unambiguous structural characterization. It was demonstrated that arabinans contain β-(1→3)-linked arabinobiose as a side chain in quinoa seeds, while potato galactan was comprised of β-(1→4)-linked galactopyranoses which are interspersed with α-(1→4)-linked arabinopyranoses. Additionally, an oligosaccharide with two adjacent arabinofuranose units O2-substituted with two ferulic acid monomers was characterized. The isolated oligosaccharides gave further insight into the structures of pectic side chains and may have an impact on plant physiology and dietary fiber fermentation.